Partisipasi Serta Langkah Pencegahan Orang Tua terhadap Paparan Asap Rokok pada Anak Usia Dini - Andini Tri Wahyuni (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This article, titled "Parental Participation and Preventive Measures Against Cigarette Smoke Exposure in Early Childhood," aims to describe the impact of cigarette smoke exposure on the health of early childhood and analyze the role of parents in prevention efforts. This research used a literature review method, compiling data from books, journals, research reports, and related academic sources. The results of the study indicate that cigarette smoke exposure can increase the risk of respiratory disorders, reduce immunity, exacerbate asthma, and trigger various chronic diseases in children. These findings confirm that early childhood is the group most vulnerable to the dangers of cigarette smoke, both from active and passive smoking. Furthermore, the discussion demonstrates the central role of parental participation through smoking cessation, the implementation of smoke-free homes, maintaining a clean environment, and ongoing family education. Various strategies, such as evidence-based education and the use of digital media, are also considered effective in raising parental awareness. Therefore, protecting children from cigarette smoke exposure requires family commitment and the support of a healthy environment.